2009
DOI: 10.1680/macr.2008.00064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of material parameters on electrical conductivity of cement pastes and concretes

Abstract: This paper reports investigations on the influence of material parameters on electrical conductivity of cement pastes and concrete mixtures. The influence of cement type, water/cementitious materials ratio (w/cm), and the presence of fly ash as a cement replacement material on the conductivity of cement pastes is studied. The electrical conductivity-time relationships of cement pastes and concretes are expressed using a model that facilitates the extraction of initial and final conductivities, and a characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In other words, lowering aggregate volume fraction or using coarser aggregate leads to thicker ITZ. Manchiryal and Neithalath 42 reported that increasing the volume fraction of sand tends to decrease the overall conductivity of mortar. Besides the increased tortuosity, the reduced ITZ extent may also be taken into account when explaining such a phenomenon.…”
Section: -44mentioning
confidence: 99%
“…In other words, lowering aggregate volume fraction or using coarser aggregate leads to thicker ITZ. Manchiryal and Neithalath 42 reported that increasing the volume fraction of sand tends to decrease the overall conductivity of mortar. Besides the increased tortuosity, the reduced ITZ extent may also be taken into account when explaining such a phenomenon.…”
Section: -44mentioning
confidence: 99%
“…Further details of the experimental set up and measurement details can be found in [7,10]. The electrical impedance measurements of concretes were carried out on cylindrical specimens with steel rods acting as electrodes.…”
Section: Electrical Impedance Measurementsmentioning
confidence: 99%
“…A more gradual decrease occurs thereafter, as hydration slows. Details on the analysis of the factors influencing electrical conductivity as a function of time, and the use of conductivity-time relationships to infer microstructural changes at early ages can be found in [7,10].…”
Section: Electrical Impedance Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former supposes that the time corresponding to the minimum value point and a turning point on the resistivity development curve is linearly related to the initial and final setting time; while the latter considers that the first peak value of the resistivity differential curve is the turning point of cement paste hardening, which is related to the final setting time of cement paste. Some studies [15,16] proposed using a derivative of the conductivity-time curve to predict the setting time of concrete. They found that the initial setting time corresponds to the highest peak of the conductivity differential curve.…”
Section: Introductionmentioning
confidence: 99%